Clinical Characteristics and Short-Term Outcomes of COVID-19 Positive Hospitalized Hemodialysis Patients (Mugda Medical College Journal, 2025)
Presentation of Novel Corona virus disease (COVID-19) and its clinical features and outcomes were different in maintenance hemodialysis (MHD) patients than in general population due to relative immunosuppression and high prevalence of co-morbidities in MHD patients. The aim of this study is to identify the clinical characteristics and outcome of MHD patients requiring hospitalization for COVID 19. In this retrospective observational study, a total of 100 adult patients of both sex who were on maintenance hemodialysis therapy having A-V fistula or permanent venous catheter admitted in Nephrology department of Mugda Medical College Hospital due to COVID-19 from April 21, 2020 to April 30, 2021 were included. Demographic data (age, sex, comorbidities), initial clinical presentations (fever, cough, shortness of breath, fatigue), oxygen saturation, chest radiograph and laboratory tests CBC, RBS, Serum Creatinine, SGPT, CRP, LDH, D dimer, Ferritin, Albumin at admission and during hospital stay were retrieved from patient file. Treatment of these hemodialysis patients was given and modified according to the hospital treatment committee including Nephrologist and Medicine specialist. As the patients were followed up from admission in hospital until discharge or death, so they were divided in two groups- Survived and death. All data were compiled and edited meticulously using SPSS version 27 software. The mean age of the patients was 53.8±13.3 (Range 15-90). Male and female ratio was 1.7.1. No significant difference was observed regarding age and sex of the study subjects. Most patients had HTN (78%) followed by DM (52%), IHD (42%), CLD (24%), pulmonary disease (21%) and Stroke (6%). The most common symptoms during admission in hospital were fever 65%, cough 52%, fatigue 43%, SOB 35% and diarrhea 8% respectively. Fever, cough, fatigue and SOB and in case of co-morbidities only IHD were statistically significant. Mean Oxygen saturation during admission was statistically significantly lower in death group (96.0±1.32 vs 90.2±2.9; p